Data Fusion Algorithm of Privacy Protection Based on Qos and Multilayers Hierarchically. (11th December 2013) - Li, Li; Qin, Qin; Hua, Li; Jian, Li
Because of the special nature of wireless sensor networks, data fusion process is vulnerable to attacks by the destroyer, which is useful for reducing the network communication overhead and improving the data transmission efficiency. Therefore, it is very essential to provide transmission with high security and low energy consumption for sensitive data fusion in wireless sensor network. In this paper, a data fusion algorithm of privacy protection based on Query of Server (Qos) and hierarchical multilayers was put forward, which divided the required privacy protection levels according to different safety requirements, and set up hierarchical network models. In data fusion process, delay constraint was added to guarantee service quality of Qos, and this would reduce energy consumption overhead. Meanwhile, it would guarantee the accuracy of the data and reduce the probability of the whole network information exposed.